2017
DOI: 10.1097/pts.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Patient Recall of Informed Consent at 4 Weeks After Total Hip Replacement With Standardized Versus Procedure-Specific Consent Forms

Abstract: Objectives: Informed consent plays a pivotal role in the operative process, and surgeons have an ethical and legal obligation to provide patients with information to allow for shared decision-making. Unfortunately, patient recall after the consent process is frequently poor. This study aims to evaluate the effect of procedure-specific consent forms on patient's recall four weeks after total hip replacement (THR).Methods: This is a prospective study using a posttest-only control group design. Sixty adult patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…18,20,31,32 The results of our study add to the evidence for a lack of effect for written information improving knowledge after consent given that there was no statistically significant difference between the groups for mean risk recall (16% versus 13%, P = 0.49). The results of the control group of this study (13% risk recall) are the same as those of the intervention group in Pomeroy et al, 5 a finding that adds to the validity of both studies given that these groups had an identical study protocol involving different patients and researchers. In contrast to our findings, Langdon et al 8 found a statistically significant improvement in knowledge recall after consent for THR when a written information sheet (48%) was used compared with verbal information (38%) only.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…18,20,31,32 The results of our study add to the evidence for a lack of effect for written information improving knowledge after consent given that there was no statistically significant difference between the groups for mean risk recall (16% versus 13%, P = 0.49). The results of the control group of this study (13% risk recall) are the same as those of the intervention group in Pomeroy et al, 5 a finding that adds to the validity of both studies given that these groups had an identical study protocol involving different patients and researchers. In contrast to our findings, Langdon et al 8 found a statistically significant improvement in knowledge recall after consent for THR when a written information sheet (48%) was used compared with verbal information (38%) only.…”
Section: Discussionsupporting
confidence: 73%
“…This finding is not unique to our study, with multiple other article reporting that between 30% and 50% of participants could not recall a single risk after consent at follow-up of 4 weeks or less. 5,15,24,34,35 This phenomenon is likely multifactorial in nature, with the passage of time, 16,21,23 a limited ability to understand the information provided at the time of consenting, and a preference for not wanting to know about the technical aspects of surgery including complications 36,37 all contributing. Some patients would prefer not to dwell on the complications associated with surgery, and this is reflected in the fact that risks are less likely to be recalled than other information provided at the time of consenting such as benefits of surgery or duration of inpatient stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sivanadarajah et al reported that the standardised consent forms endorsed by the British Orthopaedic Association are significantly more readable and understandable than heterogeneous institutional alternatives [ 9 ]. To address this, the authors note the findings of Pomeroy et al who advocate for procedure-specific consent forms for elective orthopaedic procedures in the elective setting, with significantly higher rates of patient recall of risk factors found at four weeks post-procedure [ 13 ]. However, this is often not applicable to orthopaedic trauma, as each case presenting to the ED is independent and unique to the last [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, online teaching sessions serve the purpose of attempting to reinforce the Hawthorne effect. Increasing literature reports that virtual patient education results in improved patient recall of the consent process and procedure in question [ 13 , 15 ]. However, no such data is available in relation to orthopaedic surgeons when obtaining informed consent in written form [ 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%